Integrating YouTube as a Learning Media in Islamic Education to Improve Students’ Self-Confidence - Rifka Fitrizia Prayitno Fitrizia Prayitno; Muhammad Munif (Universitas Nurul Jadid, 2024)
Islamic Education (PAI) learning is an effective approach to developing students’ character in schools. YouTube as a digital learning medium has shown potential in enhancing students’ self-confidence in the learning process. This aims to explore the urgency, implementation, and implications of Islamic Education learning using YouTube media to improve students’ self-confidence at SDN 2 Curah Jeru, Situbondo. The research employs a descriptive qualitative method with a multi-site case study design. Data were collected through observation, in-depth interviews, and documentation. The data analysis technique includes data reduction, data display, and conclusion drawing or verification to ensure the validity of findings. The findings indicate that the urgency of using YouTube in PAI learning lies in its ability to facilitate students’ understanding of learning materials while simultaneously fostering self-confidence. The implementation is carried out through several steps, including preparing materials, utilizing YouTube videos during classroom instruction, encouraging students to create their own learning content, and uploading educational videos to the YouTube platform. Furthermore, YouTube is consistently integrated into the teaching and learning process as an innovative learning strategy. The implications of this implementation are significant. Teachers become more creative and adaptive in employing various instructional models while students demonstrate increased self-confidence and active participation in learning activities. Students can access materials anytime and anywhere, enabling flexible learning beyond the classroom. Parents also benefit by being able to monitor their children’s progress from home. Moreover, the school gains broader recognition within the community due to its innovative use of digital media in education.